2019
DOI: 10.1007/s10974-019-09526-w
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule studies: the fourth wave of muscle research

Abstract: The study of muscle and contractility is an unusual scientific endeavour since it has from the start been focussed on one problem—What makes muscle work?—and yet has needed a vast range of different approaches and techniques to study it. Its uniqueness lies in the fundamental fascination of a large scale molecular machine that converts chemical energy into mechanical energy at ambient temperature and with high efficiency that is also controlled by an exquisitely intricate yet utterly reliable regulatory system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…In the past decade, interest in developing small molecules that can act directly on the contractile apparatus have emerged. This phase of research was suggested as the “fourth wave” of muscle research [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, interest in developing small molecules that can act directly on the contractile apparatus have emerged. This phase of research was suggested as the “fourth wave” of muscle research [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that a small-molecule fast-skeletal–troponin activator, would increase muscle strength in myopathy due to mutations in contractile proteins but could also be useful by amplifying the response of muscle when neural input is otherwise diminished secondary to neuromuscular disease [ 64 ]. This is possible because, unlike cardiac muscle, skeletal muscle has the advantage of being regenerative thus muscle activation can promote muscle growth [ 65 ]. A screen for Ca 2+ sensitising agents that target fast skeletal muscle troponin by Cytokinetics yielded the following compounds: Tirasemtiv (or CK-2017357), Reldesemtiv (or CK-2127107) and CK-2066260.…”
Section: Contractile Activators As Treatments For Heart Failure Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Each tropomyosin molecule interacts with seven actin monomers, and also binds one troponin complex [39]. The troponin complex has three components, troponin-C (Tn-C), which reversibly binds calcium ions in the physiological range, troponin-I (Tn-I), which is inhibitory, and troponin T, which interacts with tropomyosin [3,39,42,43]. For more details of thin filaments see reference [39].…”
Section: Striated Muscle Sarcomeres and The Contractile Mechanismmentioning
confidence: 99%
“…Skeletal muscle actin mutations account for about 20% of congenital myopathies and occur as nemaline, intranuclear rod and/or actin myopathy, and congenital fiber-type disproportion ( 9 , 10 ). Even more importantly, cardiac actin mutations that appear in the myosin or tropomyosin-binding regions cause either hypertrophic (HCM) or dilated (DCM) cardiomyopathies ( 11 ), increasing the motivation to discover small molecules that target actin for therapeutic treatment of actin-related diseases ( 12 , 13 ).…”
mentioning
confidence: 99%